2014
DOI: 10.1002/pmic.201400004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phosphoproteome in rice pistil

Abstract: As the female reproductive part of a flower, the pistil consists of the ovary, style, and stigma, and is a critical organ for the process from pollen recognition to fertilization and seed formation. Previous studies on pollen–pistil interaction mainly focused on gene expression changes with comparative transcriptomics or proteomics method. However, studies on protein PTMs are still lacking. Here we report a phosphoproteomic study on mature pistil of rice. Using IMAC enrichment, hydrophilic interaction chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 89 publications
4
39
0
Order By: Relevance
“…Of the phosphosites detected at 0 h, 89.7% were phosphoserine, 9.9% were phosphothreonine, and 0.4% were phosphotyrosines ( Figure 1B ), and the proportions were similar at the other two sampling times. Emerging evidences have shown that the distribution ratios of phosphorylation amino acids are much conserved in plants, despite the great variety of species, tissue and treatment applied (Han et al, 2014; Lv et al, 2014; Wang K. et al, 2014; Zhang M. et al, 2014; Hou et al, 2015; Qiu et al, 2016). In the three samples, 92.9–93.3% of the peptides carried only one phosphorylation group, 6.5–6.8% of the peptides carried two phosphorylation modifications, whereas only less than 0.3% of peptides had more than two phosphorylation modifications ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the phosphosites detected at 0 h, 89.7% were phosphoserine, 9.9% were phosphothreonine, and 0.4% were phosphotyrosines ( Figure 1B ), and the proportions were similar at the other two sampling times. Emerging evidences have shown that the distribution ratios of phosphorylation amino acids are much conserved in plants, despite the great variety of species, tissue and treatment applied (Han et al, 2014; Lv et al, 2014; Wang K. et al, 2014; Zhang M. et al, 2014; Hou et al, 2015; Qiu et al, 2016). In the three samples, 92.9–93.3% of the peptides carried only one phosphorylation group, 6.5–6.8% of the peptides carried two phosphorylation modifications, whereas only less than 0.3% of peptides had more than two phosphorylation modifications ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Motif extractor (Motif-X, http://motif-x.med.harvard.edu) was used to identify overrepresented glycosylation motifs. Proteins annotated in International Protein Index (IPI) human proteome database were used as background and the significance value was set as 0.000001 (Schwartz and Gygi, 2005; Chou and Schwartz, 2011; Wang et al, 2014; Zhang et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Another phosphoproteomic study identified 139 phosphoproteins from mature pollen grains and germinating pollen in tobacco (Fila et al , 2012). Also, Wang et al (2014) performed a large scale phosphoproteomic analysis using rice pistil tissue and identified 2347 phosphorylation sites from 1588 phosphoproteins.…”
Section: Introductionmentioning
confidence: 99%